FATTY ACID COMPOSITION OF ZONOCERUS VARIEGATUS, MACROTERMES BELLICOSUS AND ANACARDIUM OCCIDENTALE KERNEL - E.I. ADEYEYE (International Journal of Pharma and Bio Sciences, 2011)
The fatty acid composition of winged termites, Macrotermes bellicosus; variegated grasshopper, Zonocerus variegatus and cashew kernel (unroasted and roasted), Anacardium occidentale were reported. Oleic acid (18:1) was the most concentrated in all the samples with (%): 49.2 (M. bellicosus), 29.3 (Z. variegatus), 65.4 (A. occidentale, unroasted) and 64.6 (A. occidentale, roasted); while stearic acid (18:0) was the least concentrated with respective values as in the above trend: 8.5, 5.7, 7.2 and 7.2. Roasting enhanced the availability of linoleic acid (18:2) from 16.0 to 17.5%. The polyunsaturated fatty acid/saturated fatty acid (P/S) values were: 0.21 (M. bellicosus), 2.19 (Z. variegatus), 0.90 (A. occidentale, roasted), showing that Z. variegatus fatty acid was the best.